Tensile and impact properties of polypropylene/microcrystalline cellulose treated with different coupling agents - Samat, Noorasikin; Marini, Che Dini; Maritho, Muna Athirah; Sabaruddin, Fatimah Atiyah (2012)
Effect of different coupling agents; silane (APS) and maleic anhydride grafted PP (MAPP) on the mechanical properties of polypropylene (PP)/microcrystalline cellulose (MCC) composites were determined and compared. The composites with low filler loadings; up to 12wt%, were prepared via melt mixing in a twin screw extruder followed by injection moulding. All composites were characterized by tensile and impact tests. It is observed that the addition of MCC decreased slightly the tensile strength but the MAPP composites showed higher tensile strength than the silane composites. In contrast, the silane improved the Young’s Modulus at higher filler content. And impact properties increased with the presence of coupling agents. These results indicate that both coupling agents affected the mechanical properties in different ways associated with different filler content.